Analisis Kesiapan Tambang Skala Menengah Di Indonesia Dalam Menghadapi Transformasi Era Digitalisasi Untuk Mewujudkan Smart Mining - ariel putra; Ruth Bunga Ranggu; Hendra Sani (Journal Teknik Dan Teknologi, 2026)
Medium-scale mining in Indonesia faces challenges in the digital era, making digital transformation and smart mining essential. This study at PT. Tambang Bumi Sulawesi aims to assess digital readiness, identify supporting and inhibiting factors, and formulate strategies toward smart mining. Data were collected through observation, interviews, questionnaires, and literature review, then analyzed using the Digital Readiness Assessment and the Digital Maturity Model (DMM) with both quantitative and qualitative approaches. The findings indicate that PT. Tambang Bumi Sulawesi is at a Moderate level (Emerging–Defined) of digital readiness. Its main strengths include digital record-keeping, data storage systems, and management support, while weaknesses lie in limited infrastructure, low digital literacy among employees, minimal IoT utilization, and the absence of a digital roadmap. Recommendations include strengthening infrastructure, improving human resource competencies, developing a long-term digital strategy, and optimizing ERP and big data to achieve sustainable smart mining.